PENGEMBANGAN VIDEO PEMBELAJARAN TARIKH BERBASIS STORYTELLING UNTUK MENINGKATKAN MINAT BELAJAR SISWA SD - Asmira Efendi; Joko Subando (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2025)
Tarikh (Islamic history) education, as a part of Islamic Religious Education (PAI) at the elementary school level, plays a vital role in instilling exemplary values and shaping students' character. However, in practice, tarikh learning is often delivered monotonously through lectures and text readings, which leads to low student interest. This study aims to develop a storytelling-based tarikh learning media in the form of video that aligns with the learning characteristics of elementary students, in order to enhance their interest and engagement in the learning process. The study employs the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The needs analysis results indicate that elementary students prefer visual and interactive story-based media. The instructional video was designed in an engaging narrative format, complemented by animations and illustrations to support the content on the secret propagation (dakwah) of Prophet Muhammad SAW. The media was validated by subject matter and media experts, and underwent limited trials with fourth-grade students at SD ASC Karanganyar. The validation results and user responses show that the developed video is valid, practical, and effective in increasing student interest in tarikh material. The study concludes that storytelling-based learning media can be an innovative solution to address the low interest in learning Islamic history at the elementary school level.